The Training for Designing Inquiry Learning Tools for Teachers of Science and Social Science in Pontianak - Hairida Hairida; Gusti Budjang; Rahmat Rasmawan (Universitas Tanjungpura, 2018)
This study was motivated by the lack of knowledge and skills of junior high school students in the city of Pontianak to design learning tools, in the form of lesson plans, student worksheets, assessments, and KIT media in science and social studies learning. The method used is the implementation of in-service in the form of training and mentoring in the development of inquiry learning tools using MGMP (teacher discussion activity)-based lesson study strategies. The results of the activity showed that the IbM program designed the inquiry learning tool for teachers who were members of the Science MGMP and the Social Sciences MGMP had achieved the expected goals, namely increasing the knowledge and skills of science and social studies teachers in designing inquiry learning tools. It is shown from the acquisition of the results of the response questionnaire and the output of the activities produced.